Analgesia and anesthesia in labor and delivery-II - Baheti, Dwarkadas (Jaypee Brothers Medical Publishers, 2014)
Anesthesiologists and anesthesia play a critical role in the modern labor and delivery unit. Cesarean deliveries require the participation of an anesthesia provider in the care of the parturient (and by extension, the fetus). In addition, the anesthesiologist plays a critical role in the care of many high-risk parturients. As part of the perinatal team.